O ensino médio no Brasil e em Minas Gerais (1996 2016): nova configuração da velha dualidade - Rafaela Campos Duarte (2017)
This dissertation aimed to capture the sense of the amendments implemented and/or proposals in high school in Brazil and in the State of Minas Gerais, between years of 1996 and 2016. And, also, to analyze the potential of the current reform, approved by law No 13415/2017, to induce changes in form, content and purpose of the high school. The research was organized in three steps: literature review, documentary research and data analysis. The review sought to establish a theoretical basis for understanding the macroeconomic context and policies and reforms directed towards high school, implemented since the end of the Decade of 1990, in particular to, discuss issues related to financing, management, curriculum, evaluation and teaching work. The documentary research was performed, in order to, characterize and analyze the changes promoted or proposed in the Organization, in the curriculum and structure, both at the national level and in State of Minas Gerais. Covered Ordinances, resolutions, laws, decrees, and other documents that affect high school. The documentary analysis made it possible to identify and understand the direction of the reforms undertaken in the Brazilian high school within the timeframe announced. Can be seen that educational policies undertaken in Brazil in the period studied were centrality in evaluation process. Such process has deepened and intensified, mainly from 2009, resulting in significant changes in the curriculum, in the forms of evaluation on school management, at work, on wage policy, in teaching career, in planning and in the collective work, among others. It was noted that, in the period studied, the ProEMI, created in the year 2009, as the spearhead of the actions that seek to reform the Brazilian high school. From it, the continuity and deepening of policies that aim to change the role of Brazilian high school, what is sought to consummate with the law No. 13415/2017, that ultimately kicks to the curricular model adopted in the period of the military dictatorship, which ensure the education and structural duality denies students the enhancement as a human being your ethics and your autonomy intellectual development and your critical thinking. However, the scope of that goal entered the text of the standard will depend on the responses of individual and collective subjects in social practice.